2009
DOI: 10.1097/scs.0b013e3181a2d77f
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Vascularization

Abstract: The goal of this study was the investigation of the arterial blood supply to the maxillary sinus to give clinicians the basis for a better understanding of the origin of vascular complications that can derive from surgical procedures at this level. The study consisted of 30 sinuses from 15 human cadavers with an age range of 59 to 90 years. To define the complex vascularization of the maxillary sinus, the afferent vascular network was injected with liquid latex mixed with red india ink through the external car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 7 publications
5
69
2
10
Order By: Relevance
“…In 2009, Rysz et al [17] studied the anastomosis on foetus cadavers, and clearly the results of the prevalence and distributions were different from the ones reported in the previous studies. Rosano et al [14,15] in 2009-2010 in cadaveric study confirmed the data reported by Solar et al [18] and Traxler et al [18] in 1999. Ilgüy et al [11] in 2013 reported measures, septa presence and that the undetection of the anastomosis on cone beam CT (CBCT) is probably caused by the small diameter.…”
Section: Introductionsupporting
confidence: 81%
“…In 2009, Rysz et al [17] studied the anastomosis on foetus cadavers, and clearly the results of the prevalence and distributions were different from the ones reported in the previous studies. Rosano et al [14,15] in 2009-2010 in cadaveric study confirmed the data reported by Solar et al [18] and Traxler et al [18] in 1999. Ilgüy et al [11] in 2013 reported measures, septa presence and that the undetection of the anastomosis on cone beam CT (CBCT) is probably caused by the small diameter.…”
Section: Introductionsupporting
confidence: 81%
“…По разным литературным данным, задняя верхняя альвеолярная артерия лежит на расстоянии от 16,4 до 19 мм краниальнее задненижнего края АГ ВЧ [11,12,61,88]. Это расстояние уменьшается по мере утраты зубов и последующей атрофии АГ, что должно быть учтено при формировании костного «окошка» и аугментации ниж-ней стенки ВЧП, если планируется синус-лифтинг с це-лью дентальной имплантации [29,84]. По мнению авто-ров, исходя из того, что при анатомическом препариро-вании не обнаруживается четкой костной стенки между СО пазухи и вплотную прилегающими к ней сосудисты-ми ветвями, последние могут не выявляться рентгеноло-гически.…”
Section: стоматология 2 2015unclassified
“…The alveolar antral artery (AAA), which is the dental branch of the posterior superior alveolar artery (PSAA), anastomoses with the infraorbital artery (IOA) to form an anastomosis which was found intraosseous (endoosseous) in 100% of cases [4,6,9,10]. Moreover, the gingival branch of the PSAA was found, but not always, anastomosed with the IOA by an extraosseous anastomosis covered by the oral mucosa [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the vascular anatomy of the maxillary sinus (MS) ensures a good understanding of the vascular complication which can occur during various surgical procedures at this level [6]. The alveolar antral artery (AAA), which is the dental branch of the posterior superior alveolar artery (PSAA), anastomoses with the infraorbital artery (IOA) to form an anastomosis which was found intraosseous (endoosseous) in 100% of cases [4,6,9,10].…”
Section: Introductionmentioning
confidence: 99%